Correction: Corrigendum: Integrative genomic mining for enzyme function to enable engineering of a non-natural biosynthetic pathway - Wai Shun Mak (Nature Portfolio, 2016)
Nature Communications 6: Article number: 10005 (2015); Published: 24 November 2015; Updated: 7 June 2016 In the original version of this Article the chemical structures of 2-ketoisovaleric acid and isobutanal in Fig. 3a were incorrect. The correct version of Fig. 3 appears below. Figure 3